Cerebral Arterial Gas Embolism due to Helium Inhalation from a High-Pressure Gas Cylinder. (8th March 2022) - Morales, Gabriel; Fiero, Marie; Albert, Jesselle; Di Gennaro, Jane; Gerbino, Anthony
Abstract : Cerebral arterial gas embolism (CAGE) is a rare but serious cause for acute neurologic deficit that occurs most often in divers who breathe compressed gas at depth or iatrogenically from a variety of invasive medical procedures. We present a rare case of CAGE caused by inhaling helium from an unregulated, high-pressure gas cylinder. Following inhalation, the patient experienced loss of consciousness, neurologic deficits, pneumomediastinum, and pneumothorax requiring transfer and treatment at a hyperbaric facility with resulting resolution of neurologic symptoms. This case highlights the importance of rapid diagnosis and hyperbaric oxygen treatment (HBO), facilitated by close coordination among community emergency departments, pediatric tertiary care centers, hyperbaric facilities, and poison control.